Eksperimen Pengaruh Sudu Ganjil dan Genap Terhadap Turbin Pelton dengan Tekanan Konstan - Niharman niharman; Antonius F A Silaen (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2021)
Abstract Electrical energy is the main energy needed for electrical equipment. Electrical energy is energy that is very important for humans because electrical energy is currently one of the basic human needs. Current power plants rely heavily on fossil materials, while availability is dwindling, and an alternative energy is needed to get electricity, namely the Pelton turbine. This study aims to obtain water power, namely the Pelton turbine and to obtain efficiency, power, TSR and torque by varying the number of blades. The result is that for 9 blades the value of Cp max = 0.71, CT max = 0.95, TSR max = 2.68, max efficiency = 71%, power P turbine max = 4.08 watts. Whereas for the 12 Blade Pelton turbine, the result is that Cp max = 0.79, CT max = 1.38, TSR max = 2.74, max efficiency = 79%, turbine P power = 4.69 watts.